2021
DOI: 10.3390/pharmacy9010030
|View full text |Cite
|
Sign up to set email alerts
|

What Is Known about Community Pharmacy-Based Take-Home Naloxone Programs and Program Interventions? A Scoping Review

Abstract: A variety of new sources describing community pharmacy-based take-home naloxone (THN) programs have emerged recently in the literature. There is a need to define the types of take-home naloxone programs being offered to support future research designs in implementing and evaluating standardized programs that fill pharmacist and patient knowledge gaps and lift current barriers for optimal community pharmacy naloxone provision. The objective of this paper is to summarize the literature on community pharmacy-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 57 publications
(257 reference statements)
1
52
1
Order By: Relevance
“…7 Barriers to expanded pharmacy naloxone distribution include lack of time, lack of renumeration and stigma. [8][9][10] Urgent action is required to address the ongoing increase in opioid-associated mortality. Our national consensus guidelines for pharmacists, published in 2020, call for naloxone to be offered to all patients receiving an opioid prescription.…”
Section: Pharmd Mscmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Barriers to expanded pharmacy naloxone distribution include lack of time, lack of renumeration and stigma. [8][9][10] Urgent action is required to address the ongoing increase in opioid-associated mortality. Our national consensus guidelines for pharmacists, published in 2020, call for naloxone to be offered to all patients receiving an opioid prescription.…”
Section: Pharmd Mscmentioning
confidence: 99%
“…7 Barriers to expanded pharmacy naloxone distribution include lack of time, lack of renumeration and stigma. 8-10…”
mentioning
confidence: 99%
“…In recent years, there have been multiple articles published on the provision of naloxone by pharmacists. In fact, there have been several scoping and systematic reviews analyzing the topic from various perspectives [10][11][12][13][14]. A 2021 scoping review by Cid et al identified 19 surveys that evaluated naloxone provision by pharmacy professionals [14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there have been several scoping and systematic reviews analyzing the topic from various perspectives [10][11][12][13][14]. A 2021 scoping review by Cid et al identified 19 surveys that evaluated naloxone provision by pharmacy professionals [14]. These surveys evaluated naloxone provision in terms of dispensing frequency, naloxone availability, pharmacy staff knowledge, barriers to provision, facilitators to provision, and pharmacy professionals' attitudes toward naloxone [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation